PERAN KEPEPIMPINAN KEPALA DESA TERHADAP PENERIMAAN INOVASI PERTANIAN - Suhita, Damayanti (Transformasi, 2016)
For the farming community leadership charismatic is identical with prestige . whatever theinstruction from a respected people will be followed by the public for all the risk , so theleadership of village heads have an important role to the decision to adopt agriculturalinnovations, because the farmers will be more confident when the information ( agriculturalinnovations ) getting from people around them rather than a strangers who they dont know , sothat the speed of adoption also depends on the activities undertaken by the instructor ofagricultural. in this case is the leader of the village (village chief)Key Words : The role of leadership, acceptance of innovation